Identification of a novel caspase cleavage site in huntingtin that regulates mutant huntingtin clearance. Issue 3 (13th November 2018) - Martin, Dale D. O.; Schmidt, Mandi E.; Nguyen, Yen T.; Lazic, Nikola; Hayden, Michael R.
ABSTRACT: Huntington disease (HD) is a progressive neurodegenerative disease that initially affects the striatum and leads to changes in behavior and loss of motor coordination. It is caused by an expansion in the polyglutamine repeat at the N terminus of huntingtin (HTT) that leads to aggregation of mutant HTT. The loss of wild‐type function, in combination with the toxic gain of function mutation, initiates various cell death pathways. Wild‐type and mutant HTT are regulated by different posttranslational modifications that can positively or negatively regulate their function or toxicity. In particular, we have previously shown that caspase cleavage of mutant HTT at amino acid position aspartate 586 (D586) by caspase‐6 is critical for the pathogenesis of the disease in an HD mouse model. Herein, we describe the identification of a new caspase cleavage site at position D572 that is mediated by caspase‐1. Inhibition of caspase‐1 also appeared to decrease proteolysis at D586, likely by blocking the downstream activation of caspase‐6 through caspase‐1. Inhibition of caspase cleavage at D572 significantly decreased mutant HTT aggregation and significantly increased the turnover of soluble mutant HTT. This suggests that caspase‐1 may be a viable target to inhibit caspase cleavage of mutant HTT at both D572 and D586 to promote mutant HTT clearance.—Martin, D. D. O., Schmidt, M. E., Nguyen, Y. T., Lazic, N., Hayden, M. R. Identification of a novel caspase cleavage site in huntingtin that regulates mutant huntingtin clearance. FASEB J. 33, 3190–3197 (2019). www.fasebj.org